Effects of Benson Relaxation Technique on the Anxiety and Hemodynamic Parameters in Women before Cesarean Section: Randomized Controlled Trial - Kheiri, Mansoure; Jafari, Hale; Dehghankar, Leila; Mohammadi , Mohadese; Aashouri Faeza, Faeza; Goli, Shahrbanoo; imeni, Malihe; Ashrafi, Zahra (Shahroud Journal of Medical Sciences, 2024)
Background: Cesarean section (CS) as a delivery method is commonly used in Iran and other countries.  Many women experience anxiety before CS. This study aimed to determine the effects of the Benson relaxation on the anxiety and hemodynamic parameters of women before CS.Methods: A two-group clinical trial was conducted with a study population consisted of 108 women waiting for CS in educational hospitals in Shahroud City, Iran. The participants were randomly allocated to two groups of control and intervention each with 31 participants. After receiving a face-to-face relaxation method by the researcher, the intervention group listened to a relaxation training audio file three to five hours before CS and exercised Benson muscle relaxation at least three times. Data were collected using a demographic characteristics questionnaire, Standard Hospital Anxiety and Depression Scale, and Hemodynamic Parameters questionnaire. The collected data were analyzed in SPSS v23 using descriptive and inferential tests.Results: The results showed that the mean and standard deviation of the anxiety score in the intervention group before the intervention was 10±2.43, which was significantly higher than that after the intervention (6.86 ± 1.45). On the other hand, the mean and standard deviation of the anxiety score in the control group before the intervention was 10±3.08 and increased to 10.19 ±3.19 after the intervention.  There was also a significant difference between the intervention and control groups in terms of the mean and standard deviation of the hemodynamic parameters scores, including systolic blood pressure index (p =0.021), diastolic blood pressure index (p = 0.010), respiratory index (p= 0.037), and heart rate index (p= 0.042) after the intervention.Conclusion: Based on the results of this study, Benson muscle relaxation significantly reduced the anxiety and hemodynamic parameters scores in the intervention group. Given that this method is uncomplicated, non-pharmacological, and inexpensive, it can be useful for pregnant women in the stressful conditions before CS.